The Strategic Partnership Agreement between the EU and Japan: the pitfalls of path dependency?. Issue 7 (9th November 2016) - Gilson, Julie
Abstract: This article examines the current attempt by the European Union and Japan to negotiate a Strategic Partnership Agreement (SPA). Sitting alongside negotiations for an Economic Partnership Agreement (EPA), this SPA represents an attempt to reignite bilateral relations between these two global powerhouses. Still confined by the origins of their institutionalised partnership in 1991, this article argues that both sides find it hard to break away from earlier functional and normative assumptions about their relative significance and about each other, in order to forge a new meaningful, overarching partnership. It examines the development of Japan–EU relations building up to the preparations for this SPA, against the background of path-dependent processes of engagement. Path dependency in its various forms 'views institutions as 'carriers of history, ' which maintain existing behavioural norms and cultural patterns throughout time'. Despite some of the problems such claims elicit, as will be explored below, this article proposes that path dependency – and a particular focus on 'imprinting' – offers a useful starting point for explaining the apparent institutional inertia and incremental change that characterise much of this bilateral relationship today.